Healthy lifestyle decreases the risk of the first incidence of non-communicable chronic disease and its progression to multimorbidity and its mediating roles of metabolic components: a prospective cohort study in China - Chong Lai; Ruiyi Fu; Changzhen Huang; Lu Wang; Haiqing Ren; Yimin Zhu; Xuhui Zhang (Elsevier, 2024)
Objectives: To identify the influence of healthy lifestyles on the incidence of the first NCD (FNCD), multiple chronic conditions (MCCs), and the progression from FNCD to MCCs. Design: cohort study. Setting: Zhejiang, China Participants: 10566 subjects (55.5 ± 13.5 years, 43.1% male) free of NCDs at baseline from the Zhejiang Metabolic Syndrome prospective cohort. Measurements: Healthy lifestyle score (HLS) was developed by 6 common healthy lifestyle factors as smoking, alcohol drinking, physical activity, body mass index (BMI) and waist-to-hip ratio (WHR). Healthy lifestyle data and metabolic biomarkers collected via a face-to-face questionnaire-based interview, clinical health examination and routine biochemical determination. Biochemical variables were determined using biochemical auto-analyzer. Participants were stratified into four group based on the levels of HLS as ≤2, 3, 4 and ≥5. Multiple Cox proportional hazards model was applied to examine the relationship between HLS and the risk of FNCD, MCCs and the progression from FNCD to MCCs. The population-attributable fractions (PAF) were used to assess the attributable role of HLS. Mediating effect was examined by mediation package in R. Results: After a median of 9.92 years of follow-up, 1572 participants (14.9%) developed FNCD, and 149 (1.4%) developed MCCs. In the fully adjusted model, the higher HLS group (≥5) was associated with lower risk of FNCD (HR = 0.68 and 95% CI: 0.56−0.82), MCCs (HR = 0.31 and 95%CI: 0.14−0.69); and the progression from FNCD to MCCs (HR = 0.39 and 95%CI: 0.18−0.85). Metabolic components (TC, TG, HDL-C, LDC-C, FPG, and UA) played the mediating roles with the proportion ranging from 5.02% to 22.2% for FNCD and 5.94% to 20.1% for MCCs. PAFs (95%CI) for poor adherence to the overall healthy lifestyle (HLS ≤ 3) were 17.5% (11.2%, 23.7%) for FNCD, 42.9% (23.4%, 61.0%) for MCCs, and 37.0% (15.5%, 56.3%) for the progression from FNCD to MCCs. Conclusions: High HLS decreases the risk of FNCD, MCCs, and the progression from FNCD to MCCs. These effects are partially mediated by metabolic components. Maintaining healthy lifestyles might reduce the disease burden of common chronic diseases.